Sabellidae (Annelida: Polychaeta) living in blocks of dead coral in the Coiba National Park, Panamá - Capa, María; López, Eduardo (Journal of the Marine Biological Association of the United Kingdom, 2004)
During a study devoted to the characterization of the polychaete fauna associated with dead coral (Pocillopora spp.) in the Coiba National Park (Pacific coast of Panamá), nine species belonging to seven genera of sabellids (Annelida: Polychaeta: Sabellidae) were found. Three species new to science are described. Amphicorina bichaeta sp. nov. is characterized by having three pairs of radioles, smooth collar, broad thoracic notochaetae of two kinds (plus bayonet chaetae), and abdominal uncini with a large anterior tooth. Amphicorina perkinsi sp. nov. is characterized by having four pairs of radioles, six to eight abdominal chaetigers, smooth and oblique collar, broad thoracic notochaetae and thoracic uncini with main fang surmounted by a distinct subdistal tooth and a curved row of little teeth. Amphiglena jimenezi sp. nov. is characterized by having long radiolar appendages, medium-sized handles in thoracic uncini, and gametes in middle abdominal segments. Another six species are recorded: Branchiomma cf. bairdi and Notaulax occidentalis, which are new for the Pacific Ocean, while Notaulax nudicollis and Megalomma circumspectum, are new for the Pacific coast of Panamá. The presence of Bispira melanostigma and Pseudopotamilla intermedia is verified.
AnnelidaBase